Praktik Kerja Mahasiswa: Perwujudan Partisipasi Perguruan Tinggi dalam Pelaksanaan Pemerintahan di Tingkat Desa - Hendrikus Hironimus Botha; Flerencia G. Mamoh; Dalmasius Banusu; Yoakim Rembu; Yohanes Fritantus; Handrianus Vianey Melin Wula (Jurnal Atma Inovasia, 2026)
This article aims to describe the implementation of student internship activities at the Faculty of Social and Political Sciences, Timor University. One of the locations for student internship is in Bonibais Village, Laenmanen District, Malaka Regency. This activity was carried out based on several stages, including planning and mapping problems, field observations, implementation of field internships, and evaluation of student internship activities. The results of the activities were the implementation of all work programs designed by the Student Internship Team, namely administrative arrangement, population data collection, local potential data collection, and arrangement of the Bonibais village office environment. From the results of this activity, it was recommended to the Bonibais Village government to utilize existing local potential to improve the community's economy